Discovery of the teleosauroid crocodylomorph from the early Jurassic of Chaara cave, Middle Atlas of Morocco - (:unkn) unknown (My University, 2022)
The Chaara cave is a natural karst cavity, located in the Middle Atlas of Morocco, shaped by water over millions of years. It is an active underground river, containing several galleries spread over two floors. The exploration of this cave led to the discovery of a teleosauroid crocodylomorph at the level of the dolomitic limestone of the earliest Jurassic (Hettangian-Sinemurian). A detailed paleontological study of the specimen's skull and nested mandible was carried out based on combinations of key morphological characteristics, but to the material does not allow an advanced assignment the Moroccan specimen to a genus level. A geological, topographical, and photogrammetric study was also carried out for the development of this discovery, which is a first in the region. A 3D model of the findings was made to reconstruct this finding. The extraction of the fossil is not possible, a molding was made to keep its imprint and allow its development as a paleontological heritage. Most known teleosauroids have been recovered from Europe, and they are particularly rare outside of Europe. In Africa, they are known from several localities in Tunisia, Ethiopia, Morocco and Madagascar. Most of the remains are fragmentary and only three species have been named, Machimosaurus rex, Machimosaurus nowackianus and Steneosaurus baroni. The temporal and geographical appearance of the first thalattosuchian in Africa remains highly discussed and not well understood thus, the discovery of new remains in Morocco in the dolomitic limestone of the earliest Jurassic is of great interest, as it represents the oldest known African thalattosuchian. It demonstrates that the geographical origin of thalattosuchians cannot currently be assessed because they were widely distributed as soon as the earliest Jurassic.
Keywords: African Research